"Voy a empeñar la Edad de Oro": Historia, música y política en la crisis española (2011–2016). Issue 3 (3rd July 2017) - Fernández, Fruela
ABSTRACT: Spain's current economic and social crisis has involved a profound reappraisal of the country's history, institutions, and official narratives, especially after the emergence of the 15M or indignados movement in 2011. A crucial example of this shift has been the widespread criticism of Spain's "Transition to Democracy" or Transición, widely considered Spain's "foundational" narrative. In this article, a series of examples from the musical field—including essays, songs, and public uses of music—are studied and contextualized in order to analyze different interpretations and critiques of the Transición developed by artists, intellectuals, and politicians who took part in the 15M or have been influenced by its "climate" (Fernández Savater). In these examples, two complementary trends are identified: on the one hand, an intention to reclaim part of the Transición's collective mood through its musical symbols; on the other, a rejection of its political legacy, as expressed in criticisms of its musical canon.